Pharmacognostical studies on stem and stem bark of lagerstroemia speciosa (l.) persoon - Wahi A.K.; Khosa R.L.; Mohan Y. (My University, 2025)
Pharmacognostic studies on the stem and stem bark of Lagerstroemia speciosa (L.) Pers. has been carried out along with fluorescence characteristics, ash and extractive values. © 1982 Informa UK Ltd All rights reserved: reproduction in whole or part not permitted.